Septicemia secondary to Vibrio cholerae (non-O1/non-O139) in wound - Azeem, Ahad (BMJ Case Rep, 2019)
A 63-year-old woman with a prior history of chronic lower extremity lymphedema came to the hospital for evaluation of new-onset left leg pain and swelling associated with haemorrhagic blisters and foul-smelling discharge. Relevant history included a recent trip to a Hudson River Valley beach in New York 1 week prior to hospitalisation. Laboratory evaluation revealed significant leukocytosis and lactic acidosis. She was found to have sepsis and bacteremia secondary to Vibrio cholerae (serotype non-O1, non-O139). During a prolonged intensive care unit course requiring intravenous pressor support and broad-spectrum antibiotics, she underwent debridement of her left foot eschar along with skin grafting. Once clinically stable and improved, she was discharged to a subacute rehabilitation centre with close follow-up for wound care. V. cholerae infection is rare and often benign but can be transmitted from contaminated seawater to individuals with underlying chronic illness and cause severe symptoms, including sepsis.